2004
DOI: 10.1016/j.crte.2004.10.015
|View full text |Cite
|
Sign up to set email alerts
|

Groundwater arsenic contamination on the Ganges Delta: biogeochemistry, hydrology, human perturbations, and human suffering on a large scale

Abstract: Over the last several decades, much of population of Bangladesh and West Bengal switched their water supply from surface water to groundwater. Tragically, much of the region's groundwater is dangerously contaminated by arsenic, and consumption of this water has already created severe health effects. Here we consider how groundwater flow may affect arsenic biogeochemistry and we compare the vertical patterns of groundwater chemistry at our intensive study site with the average values across the country. Detaile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
151
1
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 193 publications
(165 citation statements)
references
References 16 publications
(48 reference statements)
12
151
1
1
Order By: Relevance
“…However, it should be noted that as all groundwater and surface water samples were collected at the same time of the year, no study of seasonal trends was undertaken. The groundwater δ 18 O range of the ECW is within the range of monsoon precipitation composition range of Mukherjee (2006) and Sengupta and Sarkar (2006) during 2004-2005. This indicates that groundwater of the area is probably recharged primarily from precipitation with similar isotopic composition to the present.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…However, it should be noted that as all groundwater and surface water samples were collected at the same time of the year, no study of seasonal trends was undertaken. The groundwater δ 18 O range of the ECW is within the range of monsoon precipitation composition range of Mukherjee (2006) and Sengupta and Sarkar (2006) during 2004-2005. This indicates that groundwater of the area is probably recharged primarily from precipitation with similar isotopic composition to the present.…”
Section: Discussionmentioning
confidence: 69%
“…The slight deviation of the samples from the LMWL suggest that some evaporation of rainfall occurs prior to or during infiltration, or there might be some mixing of the infiltrating water with preexisting soil moisture that has undergone several cycles of evaporation and wetting. Harvey et al (2005) concluded that the recharge in their study area in Bangladesh is very complex: in addition to direct infiltration from precipitation, recharge may also take place from the bottom of ponds, ox-bow lakes, rivers, and re-infiltration of groundwater withdrawn for irrigation. Such a scenario is probably also true for the present wetland especially in areas where the top aquitard is absent and the piezometric surface is below the water table of the aquitard.…”
Section: Discussionmentioning
confidence: 99%
“…That reduction of Fe and Mn oxides, a governing process for As mobilization has not been fully supported is due to several controversial points; e.g., weak relationship between dissolved As and Fe [5,14]; source of organic matter -either sedimentary organic matter or infiltration of labile organic carbon [4,46,51], dissolved Fe, chemical form of reduced Fe oxyhydroxides [24,42], and transportation process of As [52]. Given the previous studies and the present results, we conclude that the spatial variation of redox conditions and the subsequent inconsistent distribution of As and dissolved Fe in groundwater of the upper aquifer are attributable to a range of pressures.…”
Section: Mechanism Of Arsenic Mobilizationmentioning
confidence: 99%
“…recent inflow of labile organic C into groundwater due to pumping for irrigation to shallow aquifers containing As-bearing iron oxyhydroxide, can cause significant release of As to groundwater [4,32,52]. Arsenic leached out of the upper muddy layer is translocated to the lower sand (aquifer) that may be expedited by infiltrated PO 4 3 fertilizer-enhanced movement of As from the muddy layer [27,31].…”
Section: Mechanism Of Arsenic Mobilizationmentioning
confidence: 99%
“…4,5 For example, in Bangladesh, the arsenite released into the ground water contaminates drinking water, thus causing serious water problems. 6 Arsenate is a chemical analogue of phosphate, and may interfere with oxidative phosphorylation. 1 Accordingly, under the phosphate limited condition, some microorganisms, such as phytoplankton and bacteria, uptake dissolved arsenate through their phosphate-concentrating mechanisms.…”
Section: Introductionmentioning
confidence: 99%